Low temperature isothermal ageing in shape memory CuAlNi single crystals - Gastien, Rosana (2010)
Some CuAlNi alloys can undergo martensitic transformations by cooling or by applying stress from a metastable β body-centred cubic (bcc) phase. These martensitic transformations are responsible for the shape memory and pseudoelastic effects that these alloys present. Low temperature isothermal ageing of this metastable β phase can favor the culmination of an ordering process and the decomposition into stable phases. These two processes can generate changes in both thermally and stress induced martensitic transformations, modifying the characteristic martensitic transformation temperatures, the type of induced martensitic phases, the critical stress and the hysteresis width of the martensitic transformations.